SOCIOPRAGMATIC FEATURES OF ACADEMIC DISCOURSE IN ENGLISH AND UZBEK (SCIENCE TIME JOURNAL, 2026)
Language functions not only as a means of communication but also as a tool for expressing social relations and speaker intentions. This study investigates the sociopragmatic features of academic discourse, focusing on the interaction between linguistic choices and social factors. The research provides a comparative analysis of English and Uzbek academic discourse, identifying both universal principles and culture-specific characteristics. Using theoretical and discourse analysis, including examples from literary texts, the study demonstrates how social context, politeness strategies, and communicative norms influence academic communication. The findings reveal that while both languages share core features such as objectivity, logical coherence, and terminological precision, their realization differs due to sociocultural and communicative traditions.